16: A Randomized Double-Blind Trial Comparing the Effect on Pain of an Oral Sucrose Solution Versus Placebo in Children One to Three Months Old Needing Venipuncture. Issue 6 (1st June 2014) - Desjardins, M; Gaucher, N; Curtis, S; Le May, S; Lebel, D; Gouin, S
Abstract: BACKGROUND: Oral sweet solutions have been accepted as effective analgesics for procedures in the neonatal population. While the evidence of effect has been established in neonates, there have been a limited number of published clinical trials in older infants for the painful procedures commonly performed in any setting and these few studies have shown conflicting results. OBJECTIVES: To compare the efficacy of an oral sucrose solution versus placebo in reducing pain in children one to three months of age during venipuncture in the Emergency Department (ED). DESIGN/METHODS: A single-center, randomized, double-blind, placebo controlled clinical trial was conducted in an urban tertiary care pediatric university-affiliated hospital ED. The study population was all infants from one to three months of age requiring venipuncture as part of their planned ED management. Study participants were randomly allocated to receive 2 mL of 88% sucrose solution or 2 mL of a placebo solution orally, 2 min before the procedure. The primary outcome measure was the difference in pain levels during venipuncture as assessed by the Face, Legs, Activity, Cry and Consolability Pain Scale (FLACC) 1 min post venipuncture. Secondary outcome measures were the difference in pain levels using the Neonatal Infant Pain Scale (NIPS) 1 min post venipuncture, crying time and variations in heart rate following the procedure. RESULTS: Eighty-seven participants were recruited, 45 in the sucrose group and 42 in the placebo group. Overall, both groups had similar baseline demographic and clinical characteristics, including administration of pacifier and other analgesia. The mean difference in FLACC pain scores compared to baseline was 2.07±0.77 in the placebo group vs. 1.36±0.59 in the sucrose group (P=0.49). For the NIPS pain score, it was 1.73±0.62 in the placebo group vs. 0.75±0.58 in the sucrose group (P=0.36). The difference in the mean crying time following venipuncture was statistically significant between both groups (69±13 s in the placebo group vs. 49±13 in the sucrose group; P=0.04). No significant difference was found in the difference of participants' heart rates one minute post venipuncture compared to baseline (18±4 beats/min for placebo vs. 16±4 for sucrose; P=0.74). No significant adverse effects were reported. The overall blinding was successful. CONCLUSIONS: In children one to three months of age undergoing venipuncture in the ED, administration of an oral sweet solution did not statistically decrease pain scores as measured by the FLACC and NIPS scales or participants' heart rates. However, crying time was significantly decreased by providing sucrose instead of a placebo.